1995
DOI: 10.1103/physrevc.52.3167
|View full text |Cite
|
Sign up to set email alerts
|

Prescission charged particle emission inF19+232

Abstract: The multiplicities of prescission protons and n particles in the reaction ' F+ Th at 104, 110, 116, and 118 MeV have been measured. The observed multiplicities are much larger than the prediction of the statistical model without the introduction of fission delay. An analysis of the prescission proton and u data along with that for neutrons (measured earlier) has been made using deformed optical model and deformation-dependent particle binding energies. Simultaneous fits to the charged particle and neutron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…These ingredients involve the level density, the trasmission coefficients and the fission barrier models. Furthermore, estimates of τ d ,o rt h e fission time scale of the specific model, are often quite blurred by the fact that different sets of input parameters provide equally good fit to the data within the same model [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ingredients involve the level density, the trasmission coefficients and the fission barrier models. Furthermore, estimates of τ d ,o rt h e fission time scale of the specific model, are often quite blurred by the fact that different sets of input parameters provide equally good fit to the data within the same model [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Statistical Model (SM) is widely used to support the picture of a heavy-ion-induced fission process governed by nuclear viscosity [1][2][3][4][5][6][7][8][9][10][11][12]. The excess of measured prescission light particles and GDR γ-rays multiplicities with respect to the expected values determined by the SM is usually ascribed to the increment of the lifetime of the hot fissioning nucleus because of the viscosity of the nuclear matter, a physical ingredient not included in the SM.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the extensive work, estimates of the fission time scales are however quite controversial, ranging from 5 to 500 × 10 −21 s, depending on the system and on the experimental probe. Furthermore, such estimates are weakened by the fact that different sets of input parameters can result in equally good fits within the same model [3,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of studies [1][2][3][4][5][6][7][8][9][10] on the fission decay of composite systems with A≈180-250 has shown that the pre-scission multiplicities of neutrons and charged particles increase monotonically with the bombarding energy in contrast with the calculations of the statistical model (SM). This finding is considered as the evidence that fission is a slow process with respect to the lifetime for the emission of light particles.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the excitation energy, temperature, and angular momentum, the CN may tend towards the fission process [3]. Detection of charged particles as well as neutrons is used as a probe to investigate the statistical and dynamical processes of the excited nucleus [4]. The total energy carried away by the emitted particle will depend upon the Q-value and the kinetic energy of the fission fragments.…”
Section: Introductionmentioning
confidence: 99%